FREQUENCY AND ANTIMICROBIAL RESISTANCE PATTERN OF SALMONELLA TYPHI ISOLATED FROM BLOOD CULTURES - Murtaza Khan; Faisal Iqbal Afridi; Jawaid Abu bakar Warind; Qamar Jamal (Pakistan Journal of Medicine and Dentistry, 2019)
Background: